(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Introduction: Wheezing in children under five years is a common and heterogeneous respiratory problem, ranging from transient infection-related episodes to recurrent phenotypes influenced by environmental and developmental factors. Studying its spectrum is important for early clinical classification, risk identification, and prevention planning in tertiary care settings. Aim and Objective: To study the spectrum and case burden of wheeze in children aged 3 months to 5 years admitted to the Department of Pediatrics at IGMC Shimla, and to classify wheeze according to clinical profile, etiology, and associated risk factors. Materials & Methods: This observational cross-sectional study was conducted over one year from November 2024 to October 2025 in a tertiary care center in high altitude setting. A total of 151 children aged 3 months to 5 years admitted with definite wheeze were enrolled after parental consent. Both first episode and recurrent wheezers were included. Children with severe critical illness, structural airway anomalies, major cardiovascular disease, or age outside the study range were excluded. Results: Wheezing admissions occurred throughout the year, with peaks in April (14.6%), September (13.9%), and July (12.6%). Acute bronchiolitis was the commonest diagnosis (56.29%), followed by pneumonia (24.5%) and asthma (15.23%). Previous wheeze was present in 54.97% of children, while 82% had fewer than three episodes in the previous year. Hypoxemia at admission was seen in 80.79%. Episodic wheeze predominated, and environmental smoke exposure showed an important association with wheeze pattern. Conclusion: Wheezing illness in under-five children was predominantly infection-driven, with bronchiolitis and pneumonia contributing most cases. Episodic viral wheeze was the dominant phenotype, while smoke exposure, family history of recent URI, emerged as modifiable influences, supporting phenotype-based evaluation and targeted preventive strategies.